Kualitas Layanan Sirkulasi Berdasarkan Keterampilan Pustakawan di Perpustakaan Universitas Sarjanawiyata Tamansiswa Yogyakarta - Rani Kurnia Vlora (Pustabiblia: Journal of Library and Information Science, 2017)
This study aims to determine the quality of service based on the skills of the librarian in the University library Sarjanawiyata Tamansiswa Yogyakarta. This research uses descriptive qualitative research methods, techniques collecting data using interviews, direct observation and documentation. The results of this study are characteristics librarian skills that should be poured in the service are as follows: (1) with services provided in accordance with the requirements (2) Oriented to the user. (3) Ongoing rapid time and on target. (4) Walking is easy and simple. (5) Cheap and economical. (6) Attractive, fun, and creates a feeling of sympathy. (7) varied. (8) Suave. (9) Characteristically innovative and direct. (10) able to compete in the field of the other. (11) Ability to foster a sense of trust for users, to be independent and to develop new things if those characteristics as a whole are met then the quality of service is categorized as “very good” and if only some characters met then categorized as “good” and if only a little bit of character above are met then it will be categorized as “fair”. In conclusion The quality of service based on the skills of librarians in the library UST can be categorized as “good” because it meets most of the overall criteria such as: attractive, Participate in every workshop and seminar on libraries and librarianship, Endeavor mastering technological, oriented to the user and Courtesy and decisively against violations.